Hubungan Kadar Magnesium Serum Dengan Luaran Jangka Pendek Pasien Stroke Iskemik Di Manado - Dompas, Aprillia; Ngantung, Denny Jefferson; Mawuntu, Arthur Hendrik Philips (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Relationship between serum magnesium (Mg) level and short-term outcome of ischemic stroke (IS) has not been studied frequently and therefore interesting to investigate. Methods: A prospective cohort study of subjects with acute IS was conducted at Prof. Dr. R.D Kandou General Hospital, Manado, Indonesia between October 2019 and April 2020. Mg serum level of eligible subjects were examined and the National Institute of Health Stroke Scale (NIHSS) scores periodically assessed for three weeks. Relationship between serum Mg levels and all NIHSS measurements was assessed through bivariate analysis continued with linear regression. Results: There were 65 subjects (33 male) with a mean age of 57,9 years. The median onset of SI was 24 hours before hospital admission. Median systolic blood pressure was 150mmHg. The mean serum Mg level was 1.96mg/dl, with 8 subjects were hypomagnesemia. An increase in serum Mg increases baseline NIHSS score but not statistically significant (p=0,06). This value also correlates with the magnitude of changes in the initial and week III NIHSS scores (p=0,04). Conclusion: IS patients generally have normal serum Mg levels. Higher the serum Mg level, greater change between baseline NIHSS score and week III as of worsening the outcome.